Carbon quantum dot supported semiconductor photocatalysts for efficient degradation of organic pollutants in water: a review - Sharma, Sheetal; Dutta, Vishal; Singh, Pardeep; Raizada, Pankaj; Rahmani-Sani, Abolfazl; Hosseini-Bandegharaei, Ahmad; Thakur, Vijay Kumar (Elsevier, 2019)
Semiconductor photocatalyst mediated advanced oxidation processes are regarded as one of the most efficient technologies to mitigate organic pollutants in water. However, poor activity under visible light and the recombination of photogenerated electron and hole pairs hinder large scale applicability of semiconductor photocatalysts for water purification. The modification of semiconductor photocatalysts with carbon quantum dots (CQDs) is of high importance due to low toxicity, aqueous stability, enhanced surface area, economic feasibility, good biocompatibility and chemical inertness of CQDs. In this review, we highlight strategies to improve the activity of conventional semiconductor photocatalysts via coupling with CQDs. The enhanced photocatalytic activity of CQD modified narrow and wide band gap photocatalysts is due mainly to up-conversion photoluminescence (UPCL) and the electron reservoir properties of CQDs, while in the case of Z-scheme photocatalysts CQDs act as an electron mediator. Finally, a conclusive outlook and suggested research directions are provided to address challenges such as the inadequate separation of photoinduced charge carriers.
Keywords: Semiconductor photocatalysis; Limitations of conventional photocatalysts; Carbon quantum dots modified photocatalysts; Improved photocatalytic activity; Wastewater treatment